Mobile Phone Sensing using the Built-in Camera - Katuk, Norliza; Zakaria, Nur Haryani; Ku-Mahamud, Ku-Ruhana (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Modern mobile phones or smartphones have multipurpose functions apart from being used as a device for voice and text communications. They are also embedded with many useful sensors, including camera, barometer, accelerometer, and digital compass. Unlike other types of sensor, the smartphone camera has been underutilized. This paper aims to fill the gap by analyzing and reviewing the hardware and software components of smartphones and highlighting the potential uses of the smartphone camera to support human daily life activities. A simple search of research papers indexed in Google Scholar was carried out using guided terms. The papers were filtered to match the research questions for this study. Only relevant papers were analyzed and reviewed. The results of the analysis suggested that the rapid development in the smartphone hardware has extended the use of the smartphone cameras beyond personal and social photography. Consequently, applications (apps) based on smartphone cameras emerge, such as barcode readers, document digitizing tools, augmented reality, translation tools, and indoor positioning device. These apps benefit users and facilitate them in their daily life activities.